INNOVATIVE METHODS AND THEIR ROLE IN TEACHING FOREIGN LANGUAGES - Abdirazzoqova Muslima; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article describes innovative methods of teaching foreign languages in schools, academic lyceums and higher educational institutions and their advantages.